Paws and prejudice - Martin, Alanna (Martin, Alanna. Hearts of Alaska., 2021)
Enlisted by her family to help Ian Roth get his brewery off the ground, Helen, Alaska native Kelsey Porter, along with her three rescue huskies, begins to thaw towards this man and must choose between protecting her heart or mushing head-on into love.